Review of the genus Jarilla Rusby (Caricaceae) - Diaz Luna, Carlos Luis; Lomeli Sencion, Jose Aquileo (Instituto de Ecología, A.C., 1992)
A critical taxonomic revision of the genus Jarilla Rusby is made, recognizing the following species as valid: J. heterophylla (Cerv. Ex La Llave) Rusby, J. caudata (Brandegee) Standley and J. chocola Standley. A natural hybrid between J. heterophylla and J. caudata is described.